Safety and Efficacy of First-Line Treatments for Chemotherapy-Naive Metastatic Castration-Resistant Prostate Cancer: A Systematic Review and Indirect Comparison. (7th December 2017) - Zheng, Haofeng; Chen, Jialiang; Qiu, Wenhan; Lin, Sijie; Chen, Yanxiong; Liang, Guancan; Fang, Youqiang
Abstract : Recently, several drugs have been introduced for the first-line treatment of chemotherapy-naive metastatic castration-resistant prostate cancer (mCRPC), but few studies have compared treatment outcomes directly. This indirect comparison among 10 clinical trials (n = 4870 patients) retrieved from PubMed, Web of Science, Cochrane Collaboration, and ClinicalTrails.gov was performed to assess the safety and efficacy of docetaxel, cabazitaxel, abiraterone, enzalutamide, and sipuleucel-T for the initial treatment of mCRPC. No significant differences in primary outcome (overall survival) were found among initial treatments. However, docetaxel had the highest probability (37.53%) of being the most effective, but at the cost of more adverse events, while enzalutamide was associated with the best secondary outcomes (prostate-specific antigen response, progression-free survival, quality of life, and adverse event profile). Thus, docetaxel is recommended as the first agent used for the chemotherapy of mCRPC, while enzalutamide is recommended as the first nonchemotherapy treatment. Additional clinical trials are needed to confirm these findings and establish the optimal order for multidrug treatment of mCRPC.